An introduction to the exploration of congregations in South Africa: seeking significance - W. J. Schoeman (Acta Theologica)
From text: It is possible to ask questions and to do research about a wide variety of topics within the study field of practical theology. An important question would be about the relevance of these research questions and findings. What difference does it make to explore within this field of practical theological investigation? The aim of this introduction is to describe a framework for doing significant practical theological research, but also to seek significance within the field of congregational studies.